Prediction of Egg Development and Mortality Rates in Capelin ( Mallotus viliosus ) from Meteorological, Hydrographic, and Biological Factors - Frank, Kenneth T.; Leggett, William C. (Canadian Journal of Fisheries and Aquatic Sciences, 1981)
We studied the factors governing in situ egg development and mortality rates in beach spawning capelin (Mallotus villosus). Time to hatching was strongly influenced by the average incubation temperature which varied between years and between cohorts in a single year, and between positions on the beach (high, mid, low tide zone). Average incubation temperatures were determined by a complex of variables which included water temperature, maximum and minimum air temperature, and hours of sunlight. Mortality rates were both spatially and temporally variable. Over 70% of the temporal and spatial variance in egg mortality was attributed to the interacting effects of egg density, water temperature, maximum and minimum air temperature, hours of sunlight, rainfall, and tidal amplitude. Multivariate equations for predicting egg mortality as a function of these variables are given. The principal climatic and hydrographic variables influencing egg mortality vary only slightly over a 7° range of latitude encompassing the main spawning sites of the eastern Newfoundland and southern Labrador coasts. The potential thus exists for synchronous year to year changes in egg mortality over this spawning range as a result of annual variations in climate and hydrographic conditions. Such synchronous changes may contribute to the substantial year to year fluctuations in capelin year-class strength.Key words: capelin, Mallotus viliosus; development, mortality, meteorology, hydrology, temperature, intertidal zone, year-class, egg, beach spawning